FEE AUDIT SEBAGAI PEMODERASI PENGARUH TIME BUDGET PRESSURE DAN AUDIT TENURE PADA SKEPTISISME PROFESIONAL AUDITOR - Fitria Ningrum Sayekti; Gina Wulan Purnama; Kevin Herdiyanto (Media Nusantara, 2022)
The goal of this research is to find out: (1) The Effect of Time Budget Pressure on the Auditor's Professional Skepticism, (2) The Effect of Audit Tenure on the Auditor's Professional Skepticism, (3) The Effect of Time Budget Pressure on the Auditor's Professional Skepticism, which is moderated by Fee Audit, and (4) The Effect of Audit Tenure against Auditor Professional Skepticism moderated by Fee Audit. In this study, a purposive sample of 50 auditors from the Public Accounting Firm (KAP) in Bandung City was used. Primary data was employed as a source of information. Data was gathered by direct distribution of surveys to respondents. Multiple regression analysis approaches were used in the data analysis technique. The findings of this study are as follows: (1) The effect of Time Budget Pressure (X1) on the Professional Skepticism of Auditors (Y), the results do not have an effect of 0.720 0.05 or the value of t count is greater than t table (0.361 1.679); (2) The effect of Audit Tenure (X2) on the professional skepticism of auditors (Y), the results obtained an effect of 0.047 0.68 or the t count value is greater than t table (1.868 1.679). (3) With the results of R Square in the first regression R Square in the second regression (0.003 0.091), Fee Audit (Z) strengthens the influence of Time Budget Pressure (X1) on Auditor Professional Skepticism (Y). With the results of R Square in the first regression R Square in the second regression (0.068 0.089), Fee Audit (Z) strengthens the influence of Audit Tenure (X1) on Auditor Professional Skepticism (Y).